Respuesta :
The value of x is "[tex]\bold{(2, \frac{21}{2})}[/tex]".
Given:
[tex]\to \frac{1}{2x-3} + \frac{5x}{2x+6} =2[/tex]
To find:
x=?
Solution:
[tex]\to \frac{1}{2x-3} + \frac{5x}{2x+6} =2 \\\\[/tex]
Taking lcm:
[tex]\to \frac{2x+6 +5x(2x-3)}{(2x-3)(2x+6)} =2\\\\\to \frac{2x+6 +10x^2- 15x}{(4x^2+ 12x-6x-18)} =2\\\\\to \frac{10x^2- 13x+6}{4x^2+ 6x-18} =2\\\\[/tex]
[tex]\to 10x^2- 13x+6 = 2(4x^2+ 6x-18)\\\\\to 10x^2- 13x+6 = 8x^2+ 12x-36\\\\\to 10x^2- 13x+6 - 8x^2- 12x +36=0\\\\\to 2x^2-25x+42=0\\\\[/tex]
compare the value with the [tex]ax^2+bx+c=0[/tex]:
[tex]\to a=2\\\\\to b= -25\\\\\to c=42\\\\[/tex]
Using formula:
[tex]\to \bold{x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}}[/tex]
[tex]\bold{=\frac{- (-25) \pm \sqrt{(-25)^2-4\times 2 \times 42}}{2 \times 2}}\\\\ \bold{=\frac{25 \pm \sqrt{ 625 - 336}}{4}}\\\\ \bold{=\frac{25 \pm \sqrt{289}}{4}}\\\\ \bold{=\frac{25 \pm 17 }{4}}\\\\ \bold{=(\frac{8}{4} , \frac{42}{4})}\\\\ \bold{=( 2 , \frac{21}{2})}\\\\[/tex]
Therefore, the final answer is "[tex]\bold{(2, \frac{21}{2})}[/tex]".
Learn more about the value x:
brainly.com/question/18681264